2018
DOI: 10.1016/j.diii.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

CT-texture analysis of subsolid nodules for differentiating invasive from in-situ and minimally invasive lung adenocarcinoma subtypes

Abstract: CTTA has the potential to differentiate AIS and MIA from IVA among SSLNs. However, our results require further validation on a larger cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…Although there was no statistically difference in kurtosis and entropy, the values of them gradually increased as tumor malignant degree increased (from pNET to PDAC). This variation trend was in accordance with previous researches . Hence, this study could provide reference value for further large sample research and contribute to the development of CTTA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although there was no statistically difference in kurtosis and entropy, the values of them gradually increased as tumor malignant degree increased (from pNET to PDAC). This variation trend was in accordance with previous researches . Hence, this study could provide reference value for further large sample research and contribute to the development of CTTA.…”
Section: Discussionsupporting
confidence: 91%
“…This variation trend was in accordance with previous researches. 26,27 Hence, this study could provide reference value for further large sample research and contribute to the development of CTTA. This study had several limitations.…”
Section: T a B L E 5 Comparison Of Area Undermentioning
confidence: 86%
“…Son et al [ 24 ] demonstrated that the 75th percentile CT attenuation value could be used to distinguish IA from pre-invasive lesions. Kurtosis, skewness, or entropy of GGNs could be used for differentiating pre-invasive lesions and IA [ 24 26 ]. In addition, advanced radiomic features including shape and morphology metrics, Renyi dimensions, geometrical measures, and the gray-level co-occurrence matrix or the gray-level run length matrix might be useful for differential diagnosis of GGNs [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on 70 adenocarcinoma patients, the proposed model achieved an accuracy of 86.3% in predicting ve histological subtypes of adenocarcinomas [9] . Then, 44 lung adenocarcinoma patients were studied by Cohen, which can differentiate AIS and MIA from IAC among subsolid lung nodules by computed tomography [10] . In addition, the segmentation techniques of computed tomographic three-dimensional (3D) indicated that computer-assisted 3D measurement of nodules at CT had good reproducibility and helped differentiate among subtypes of lung adenocarcinoma [11] .…”
Section: Backgoundmentioning
confidence: 99%